Influence of phosphorus level and weed-control method on phosphorus uptake by gobhi sarson (Brassica napus subsp oleifera var annua) and associated weeds - Rana, M C; Angiras, N N (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the winter season of 1987-89 to study the effect of weed -control methods and phosphorus levels on P uptake by gobhi sarson (Brassica napus 1. ssp oleifera DC. var annua L.) and associated weed species. Out of the 2 herbicides, pendimethalin @ 1.5 kg/ha applied at pre-emergence stage was effective in increasing the seed yield (967.2 kg/ha) and P uptake by the crop (9.6 kg/ha) by reducing the dry matter (485.7 kg/ha) and P uptake by weeds (0.6 kg/ha). But isoproturon@ 1.0 kg/ha caused phytotoxicity in crop and was less effective in controlling weeds. Among all the weed-control methods, 2 hand-weedings (40 and 70 days after sowing) significantly decreased the dry matter and P uptake of all the weed species except of common vetch (Vicia sativa L.). However, pendimethalin significantly reduced the P uptake by common vetch. An increase in P level from 0 to 35.2 kg P/ha increased P uptake by weeds from 0.3 to 1.9 kg/ha. Two hand-weedings with 26.4 kg P/ha increased the seed yield (1 464.7 kg/ha) and P uptake by gobhi sarson (15.6 kg/ha) significantly. The next best treatment combination was pendimethalin@ 1.5 kg/ha applied at pre-emergence stage along with 17.6 or 26.4 kg P/ha. Thus weed control with pendimethalin or 2 hand-weedings with. 17.6 kg P/ha resulted in P-use efficiency of 44.5 or 44.4% respectively.